2020
DOI: 10.1177/0267659120980375
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiac surgery in Jehovah’s Witness patients: A review

Abstract: Objective: To review current literature evidence on outcomes of cardiac surgery in Jehovah’s Witness patients. Methods: A comprehensive electronic literature search was done from 2010 to 20th August 2020 identifying articles that discussed optimisation/outcomes of cardiac surgery in Jehovah’s Witness either as a solo cohort or as comparative to non-Jehovah’s Witnesses. No limit was placed on place of publication and the evidence has been summarised in a narrative manner within the manuscript. Results: The outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Only two departments had local guidelines addressing clinical interventions for patients declining transfusion of blood components. This is in contrast with current knowledge that successful multidisciplinary planning and blood management reduces transfusion of blood components as well as blood loss 2,4,11,12,23,29 . Minimising blood loss perioperatively reduces risk of adverse events 1–4,10,30 …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Only two departments had local guidelines addressing clinical interventions for patients declining transfusion of blood components. This is in contrast with current knowledge that successful multidisciplinary planning and blood management reduces transfusion of blood components as well as blood loss 2,4,11,12,23,29 . Minimising blood loss perioperatively reduces risk of adverse events 1–4,10,30 …”
Section: Discussionmentioning
confidence: 87%
“…6,13,15,28 components as well as blood loss. 2,4,11,12,23,29 Minimising blood loss perioperatively reduces risk of adverse events. [1][2][3][4]10,30 Lack of local guidelines inherently force physicians to make more individual decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case law of Re C (adult: refusal of medical treatment) [1994] 1 All ER 819 (QBD) [10], it can be concluded that a clinician is to respect patient decision, even if the patient’s decision goes against the patient’s best interests in the eyes of the clinician as long as the patient is deemed to have capacity [10,11]. In cases of emergencies, where it is difficult to gain consent or unlikely for patient to have capacity, many patients who stand against use of transfusions during treatment keep an advanced directive card, which identifies their preference regarding blood transfusions, including whether they refuse all types of blood transfusion or certain components only [12].…”
Section: Respecting Patient Wishes and Risksmentioning
confidence: 99%